Piperine, a natural bioenhancer, nullifies the antidiabetic and antioxidant activities of curcumin in streptozotocin-diabetic rats - Arcaro, Carlos Alberto [UNESP]; Gutierres, Vania Ortega [UNESP]; Assis, Renata Pires [UNESP]; Moreira, Thais Fernanda [UNESP]; Costa, Paulo Inacio [UNESP]; Baviera, Amanda Martins [UNESP]; Brunetti, Iguatemy Lourenco [UNESP] (Public Library Science, 2014)
Knowing that curcumin has low bioavailability when administered orally, and that piperine has bioenhancer activity by inhibition of hepatic and intestinal biotransformation processes, the aim of this study was to investigate the antidiabetic and antioxidant activities of curcumin (90 mg/kg) and piperine (20 or 40 mg/kg), alone or co-administered, incorporated in yoghurt, in streptozotocin (STZ)-diabetic rats. The treatment for 45 days of STZ-diabetic rats with curcuminenriched yoghurt improved all parameters altered in this experimental model of diabetes: the body weight was increased in association with the weight of skeletal muscles and white adipose tissues; the progressive increase in the glycemia levels was avoided, as well as in the glycosuria, urinary urea, dyslipidemia, and markers of liver (alanine and aspartate aminotransferases and alkaline phosphatase) and kidney (urinary protein) dysfunction; the hepatic oxidative stress was decreased, since the activities of the antioxidant enzymes superoxide dismutase, catalase and gluthatione peroxidase were increased, and the levels of malondialdehyde and protein carbonyl groups were reduced. The dose of 20 mg/kg piperine also showed antidiabetic and antioxidant activities. The treatment of STZ-diabetic rats with both curcumin and 20 mg/kg piperine in yoghurt did not change the antidiabetic and antioxidant activities of curcumin; notably, the treatment with both curcumin and 40 mg/kg piperine abrogated the beneficial effects of curcumin. In addition, the alanine aminotransferase levels were further increased in diabetic rats treated with curcumin and 40 mg/kg piperine in comparison with untreated diabetic rats. These findings support that the co-administration of curcumin with a bioenhancer did not bring any advantage to the curcumin effects, at least about the antidiabetic and antioxidant activities, which could be related to changes on its biotransformation.